The determinants of non-tariff barriers in Malaysia’s manufacturing sector - Hanif, Azlina; Alavi, Rokiah; Mat Ghani, Gairuzazmi; Duasa, Jarita (2011)
The successive rounds of multilateral trade negotiations have resulted in significant tariff reductions in many countries. Malaysia is no exception as its trade weighted average tariff rate in 2008 is relatively low at 6.3 percent. Despite the reduction in tariff barrier, the incidence of non-tariff barriers (NTBs) in the country’s manufacturing sector is still prevalent especially in certain sub-sectors even though efforts at dismantling these barriers have long been initiated. Thus, the paper seeks to identify factors that influence the level of NTBs in the manufacturing sector. Using the autoregressive distributed lag (ARDL) approach to cointegration, we find sectoral competitiveness level to be the only significant determinant of NTBs in the long run. In the short run, tariff and sectoral competitiveness both influence the level of NTBs. The findings provide a greater understanding of the reasons behind trade protectionism in the country’s manufacturing sector.